Radiographic imaging & exposure - Fauber, Terri L. (Bosby, 2004)
This text provides thorough, practical coverage of fundamental principles of imaging, designed to ensure that readers grasp the information they need to produce high-quality images in the clinical setting. Features such as Practical Tips, Important Relationships, and Mathematical Solutions are presented throughout the text as appropriate and listed in the appendixes for quick reference. Additional features that set the book apart include more coverage of computed radiography and film processing, and unique film critique sections in relevant chapters.